2013
DOI: 10.1121/1.4824843
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of sound by porous layers with embedded periodic arrays of resonant inclusions

Abstract: The aim of this work is to design a layer of porous material with a high value of the absorption coefficient in a wide range of frequencies. It is shown that low frequency performance can be significantly improved by embedding periodically arranged resonant inclusions (slotted cylinders) into the porous matrix. The dissipation of the acoustic energy in a porous material due to viscous and thermal losses inside the pores is enhanced by the low frequency resonances of the inclusions and energy trapping between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(61 citation statements)
references
References 16 publications
1
60
0
Order By: Relevance
“…It has been shown that performance of porous absorbers at low frequencies can be improved by embedding the resonant scatterers. 12,13 However, the absorption of these structures varies with the angle of incidence.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that performance of porous absorbers at low frequencies can be improved by embedding the resonant scatterers. 12,13 However, the absorption of these structures varies with the angle of incidence.…”
Section: Introductionmentioning
confidence: 99%
“…Boutin and B ecot 10,11 developed a similar expression for resonant material made of HRs embedded in a foam matrix with a three-dimensional (3D) periodicity using the homogenization method. In the case of cellular resonant material with a two-dimensional (2D) periodicity, Lagarrigue et al 12 and Groby et al 13 show that the sound absorption behavior of the material can be impacted by the orientation of a) Electronic mail: olivier.doutres@usherbrooke.ca the resonator aperture. Lagarrigue et al 12 proposed an interesting 2D semi-analytical model in the case of embedded slit rings in a large periodic foam unit cell for which the slit orientation relative to the rigid backing is taken into account.…”
Section: Haisam Osmanmentioning
confidence: 99%
“…[7][8][9][10][11] Most of these works mainly focused on the transmission properties of the resonant material and highlighted the large transmission dip at the HR resonance frequency. [7][8][9] Boutin and B ecot, 11 Lagarrigue et al, 12 and Groby et al 13 recently investigated the sound absorption efficiency of rigid backed acoustic foams with resonant split hollow cylinder or HR inclusions and showed that it is greatly improved for frequencies with a wavelength much larger than the material thickness.…”
Section: Haisam Osmanmentioning
confidence: 99%
“…These specific materials are artificial structures composed of an arrangement of resonant unit cells-smaller than the characteristic wavelength-that present effective properties not observed in the materials that compose the structure. Examples of such absorbers are metaporous materials [6][7][8][9], metamaterials composed of membrane-type resonators [10][11][12][13], Helmholtz resonators (HRs) [13][14][15][16], and quarter-wavelength resonators (QWRs) [4,[17][18][19]. These last types of metamaterials [4,[15][16][17][18]] make use of strong dispersion, giving rise to slow-sound propagation inside the material.…”
Section: Introductionmentioning
confidence: 99%